2008
DOI: 10.1007/s10344-008-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of crop damage by wild boar (Sus scrofa)in Luxembourg over a 10-year period

Abstract: In many European countries, the wild boar (Sus scrofa) is often associated with crop damage. In this study, we analyse data relating to 13,276 cases of wild boar damage to agricultural crops over a 10-year period in Luxembourg (an area of 2,586 km 2 in Western Europe). Results show that (1) damage is more severe in this area than in others; (2) damage to permanent grassland is far more frequent and more severe than damage to annual crops; (3) trichomatous crops such as barley are avoided; (4) damage is seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
175
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(201 citation statements)
references
References 22 publications
23
175
2
1
Order By: Relevance
“…This is in line with previous studies, which have revealed that wild boar damage is negatively correlated with the grade of anthropogenic influence (e.g. Schley et al 2008). We think that the distance to the nearest occupied building (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with previous studies, which have revealed that wild boar damage is negatively correlated with the grade of anthropogenic influence (e.g. Schley et al 2008). We think that the distance to the nearest occupied building (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…3). This is in line with other studies that showed grassland to be damaged at higher proportions than cereal crops and other seasonal cultures (Schley 2000, Schley et al 2008. Our result also corresponds with the yearly damage statistics of the hunting and fishing agency of the Canton Basel-Land, which amounts damage to grassland at approximately 50% of all damage caused by wild boars (unpubl.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, several factors suggest that the trend is worrisome. In recent decades, populations of wild boar have increased in Europe (Geisser and Reyer 2004;Acevedo et al 2006;Schley et al 2008). Larger populations might lead to an increase in wild boar disturbances, which has been observed in feral pig populations in other protected mountainous areas (Hone 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the prof itability of hunting has encouraged certain practices such as the use of artificial feeders and the legal or illegal relocation of individuals that have increased the number of boar (Wood & Barret, 1979;Spencer & Hamton, 2005). The negative effects of increases in wild boar populations include damage to crops (Herrero et al, 2006;Schley et al, 2008), traffic accidents (Rosell et al, 2001;Peris et al, 2005;Colino-Rabanal et al, 2012), and the transmission of diseases since wild boar act as a reservoir for livestock, wildlife, and human diseases such as brucellosis, tuberculosis, salmonellosis, Aujeszky's disease, and classical and African swine fever. Some of these diseases can cause direct or indirect economic losses -mortality and poorer weight gain in livestock -and oblige the implementation of disease prevention, control, and eradication programs.…”
mentioning
confidence: 99%